CARBON STOCKS AND HYDRICAL RETENTION IN GRASS BIOMASS IN THE PARAÍBA AGRESTE MESOREGION - da Silva, P. L. F.; de Oliveira, F. P.; Pereira, W. E.; Borba, J. O. de M.; Tavares, D. D.; Santos, T. E. D.; Martins, A. F. (Brazilian Journal of Biosystems Engineering, 2019)
The management system, when improperly adopted, can lead to physical, chemical and biological soil degradation, especially in the absence of vegetation cover. The selection of grasses is a fundamental part of the production systems, mainly regarding the dry matter production and the deposition of carbon to the soil, favoring the recovery of degraded environments. Thus, the objective of this work was to evaluate the carbon stock and water retention in biomass of grasses grown in the Paraiba Agreste. The experiment was installed in an experimental area of the Center of Agricultural Sciences of the Federal University of Paraiba, Areia (PB) (6 ° 58'12''S; 35 ° 41'15''W). The design was of randomized blocks composed of the following treatments T1 - Brachiaria decumbens Stapf., T2 - Brachiaria brizantha, T3 - Brachiaria humidicola (Rendle) Schweick vr., T4 - Brachiaria brizantha cv. MG5 - Vitória e T5 - Without vegetal cover. The variables analyzed were: total organic carbon, carbon stock, dry mass production and water retention in the dry mass. According to the results, Brachiaria brizantha was superior in dry mass production and water retention capacity. Total organic carbon and carbon stock did not vary between treatments.